Slender steel columns: How they are affected by imperfections and bracing stiffness. (November 2016) - Klasson, Anders; Crocetti, Roberto; Hansson, Eva Frühwald
Abstract: Finite-element programs can be used for designing columns and their bracing systems. It is well known, however, that the output obtained from such programs is highly dependent upon the input (such as imperfections and stiffness properties). In the present study, the effects of imperfections on the predicted strength and stiffness requirements of steel columns and of their bracing systems are investigated. Two different systems are analyzed: 1) a braced non-sway column and 2) a braced sway column. It was found that a poor choice of the shape of the initial imperfections can provide unrealistic results in terms of both the buckling load on the columns and the predicted reactions of the bracings. It was also found that superimposing different imperfection shapes can contribute to obtaining realistic and trustworthy results. Furthermore, it was shown that the shapes of the initial imperfections that lead to the lowest buckling load and those that result in the strongest bracing forces, are generally not the same.